Evaluation and Comparison of Thermal Changes in the Pulp Chamber in Different Inter Proximal Reduction Techniques: An In-vitro Study - Dara, Abhilash; Datla , Praveen Kumar Varma; Priya, C. V. Padma; Manda , Anoosha; Kandikatla, Pradeep; Polineti , Priyanka (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Introduction: Interproximal reduction (IPR) is a common orthodontic treatment procedure that is used which involves tooth reduction, anatomic recontouring, and protecting permanent teeth proximal enamel surfaces. Sheridan described the air-rotor stripping technique as an alternative to extraction in borderline cases. Though there are many studies, it was not clearly differentiated regarding the pulpal temperature changes during IPR. Materials and Methods: In this in vitro study, 63 extracted human premolar teeth were randomly assigned to three groups (n=21). Group-1 (Strauss diamond stripping bur) at high speed above 20,000 rpm, Group-2 (Manual Handheld metal stripper). Group-3 (Strauss diamond stripping disc) at a low speed below 15,000 rpm. The average mean temperature is assessed for each tooth during various techniques using K-type thermocouple. During the procedure, the thermometer display was covered, and the temperature was revealed after all the stripping procedures had already been performed. Data were analyzed using IBM SPSS version 20 software. Descriptive statistics, one way analysis of variance with Tukey’s post hoc tests were done to analyze the study data. Results: The mean rise in temperature was highest with disc & micromotor (4.3ºC) followed by airotor & bur (4.02ºC) and manual method (2.52ºC) (p ≤ 0.05). Conclusion: There was an increase in the pulpal temperature using diamond stripping disc with micromotor followed by the airotor and bur, manual hand held stripping.